The MODIFICATION OF THE DRIVE SYSTEM IN AUTOMATICAL AMMUNITION CLADDING DETROYER - Lamhot Pangaribuan; Fajar Apit Firmanto; Dedi Nurdiansyah (Pustaka Poltekad, 2021)
The era of the Industrial Revolution 4.0 military power became one of the important elements because technological developments have changed the entire order of military strategy. One of them is the development of military equipment technology part of weaponry. As is known, often Indonesia army soldiers conduct shooting exercises to defend the Nation and the Unitary State of the Indonesian People (NKRI). With the shooting training there is a lot of waste from bullet cladding. Bullet cladding or patrun is an object that is a container that wraps around a bullet projectile and consists of propellant (gunpowder), rim, and primer. Bullets/munitions after firing can still be recycled back into active munitions. In accordance with the purpose of this study, researchers modified a cladding machine in order toimprove the performance of thetool effectively than before. The research methods used are a combination of experimental and empirical manual calculations to determine the relevant results. The result destruction can cut 3 grains of cladding even more in everyone round of the cutting blade, so this study modified the transmission system, fixed clutch, shaft, straight gear. The transmission uses a1:60 wpa gearbox ratio, with an electric motor drive power of 1.5 kW/ 2 HP, 1450 r / min, using a flange type clutch.